COMPARISON OF CONVENTIONAL SLAB AND METAL DECK COMPOSITE SLAB METHOD TO TIME AND COST IN TRANSPARK CIBUBUR PROJECT - Anjas Handayani; Mochamad Elvan Reza (Neutron, 2020)
in the implementation of the Transpark Cibubur project, especially in Tower C Apartment there are several problems in conventional slab methods including the need for a longer construction time. With some thoughts and considerations, the work method of floor slab was changed from conventional method to metal deck composite slab method. In this research, a comparative of conventional slab and metal deck composite slab method in Tower C of the Cibubur Transpark Project is the object of research to compare the two methods to speed of implementation and cost requirements. The analysis results show in Tower C 16th to 19th floor for metal deck composite slab method is more expensive than conventional slab method with a cost difference Rp. 137.252.215,54. While in terms of work time, conventional slab method are longer than metal deck composite slab method with a time difference for 25 days.